Sedimentologia e Estratigrafia -Estudo de um terraço de Lavadores. Contribuição para a dedução das condições paleoclimáticas no Plistocénico médio - H. Ribeiro (2010)
Sedimentological studies of the terrace of the Pedras Amarelas in Lavaores (Vila Nova de Gaia) suggest, from the bottom up and to the migration of sedimentary environments to the west, the existence of coastal intertidal sedimentation, from the river sedimentation and culminating with swampy environments/lagoon in which there is evidence periglaciation. Geochronological studies conducted by OSL and 14C dating allowed with 180±25Ka and >40Ka, respectively. The pollen content identified about 50 pollen types mostly belonging to herbaceous plants. Most notably is the presence of Asteraceae and Gramineae pollen